The Rainbow Magic collection : volume 1: books #1-4 - Meadows, Daisy; Ripper, Georgie (New York : Scholastic Inc, 2007)
After Rachel and Kirsty accidentally rescue Ruby the red fairy from under the pot at the end of the rainbow, they decide to help return color to Fairyland by rescuing her sisters from where they are trapped on Rainspell Island.
Ruby the red fairy -- Amber the orange fairy -- Sunny the yellow fairy -- Fern the green fairy.
Keywords: Fairies -- Juvenile fiction; Fiction